2017
DOI: 10.1007/s00262-017-2070-3
|View full text |Cite
|
Sign up to set email alerts
|

Absolute lymphocyte counts at end of induction correlate with distinct immune cell compartments in pediatric B cell precursor acute lymphoblastic leukemia

Abstract: Several retrospective studies in children with B cell precursor (BCP) acute lymphoblastic leukemia (ALL) provided clinical evidence that higher absolute lymphocyte counts (ALC) early into treatment significantly correlated with improved relapse-free and overall survival. It still remains unknown, however, whether the predictive role of higher ALCs reflects general bone marrow recovery or a more specific attribute of immune function. To investigate this question, we implemented a prospective observational cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The median WBC at diagnosis was 17.2 × 10 3 cell/ ul which considered high when compared to 9.22 × 10 3 cells/ul reported by Farkas et al [1] and 12.260 cell/ul by Hatzipantelis et al [12] which may be explained by a higher incidence of T phenotype among our patients. This comes true when we found that the median initial WBC count of 4300 cell/ul reported by Rolf et al [19] who studied ALC in a group of patients with B-ALL. and evaluated their impact as a prognostic factor in ALL at two different cut off levels ALC 350 (< or ≥350 cell/µl) and ALC 500 (< or ≥500 cell/µl).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The median WBC at diagnosis was 17.2 × 10 3 cell/ ul which considered high when compared to 9.22 × 10 3 cells/ul reported by Farkas et al [1] and 12.260 cell/ul by Hatzipantelis et al [12] which may be explained by a higher incidence of T phenotype among our patients. This comes true when we found that the median initial WBC count of 4300 cell/ul reported by Rolf et al [19] who studied ALC in a group of patients with B-ALL. and evaluated their impact as a prognostic factor in ALL at two different cut off levels ALC 350 (< or ≥350 cell/µl) and ALC 500 (< or ≥500 cell/µl).…”
Section: Discussionmentioning
confidence: 50%
“…Farkas et al [1] and Gupta et al [2] reported that their patients with low ALC values tend to have a higher risk (MR or HR groups) and a higher age at diagnosis (>10 years) on day 15 of induction with similar cutoff ALC value. Rolf et al [19] when investigated the relationship between D29 ALC and age as continuous variables also reported a significant inverse correlation (r = −0.47; p = 0.033). A finding that confirms the general observation that lymphocyte counts decrease with increasing age [20].…”
Section: Discussionmentioning
confidence: 90%
“…The absolute lymphocyte count (ALC) at the end of induction therapy is also reported to be a strong prognostic indicator in pediatric ALL; patients with high ALC are at significantly reduced risk of recurrence [8][9][10][11][12]. While the biology underlying this association remains unclear, we observed that the ALC was not simply a reflection of bone marrow recovery [13]; numbers of specific immune cell subsets, including T cells and dendritic cells, were most strongly correlated with ALC, suggesting a potential role for the endogenous immune system in the prevention of recurrence. Stimulation of this immune environment during early treatment could contribute to greater immune control of ALL progression.…”
Section: Introductionmentioning
confidence: 56%
“…Furthermore, the significant increase in the number of cDCs following CpG ODN treatment may represent the accumulation of mature DCs with migratory capacity capable of priming T cells required for establishing long-term protection against ALL. Notably, the cell populations implicated in the TLR-induced control of primary B-ALL in this study are present early in treatment at numbers that correlate with ALC [13].…”
Section: Discussionmentioning
confidence: 82%